Anthraimidazoledione Derivatives in Fluoride Sensing Ensuing Si‐O Bond Cleavage in Organic and Aqueous Medium. Issue 19 (15th May 2020) - Mondal, Subhendu; Roy, Saswati Ghosh; Ghosh, Kumaresh
Abstract: Anthraimidazoledione derivatives 1 and 2 containing silyl groups have been synthesized and characterized. Anion binding properties with reference to Si−O bond cleavage are documented in organic and aqueous medium. Both compounds 1 and 2 selectively sense F − ion over a series of other anions by exhibiting ratiometric change in UV‐vis spectra in CH3 CN. In fluorescence, significant quenching of emission of both 1 and 2 occurs in presence of F − . Other anions in this event are silent. Compounds are also found working in aqueous CH3 CN. Both show quenching of emission while aqueous solution of KF is added to their acetonitrile solutions. Importantly, Si−O bond cleavage in 1 and 2 follows first order kinetics and the cleavage is more facile in 1 than 2 . The detection limits for fluoride with compounds 1 and 2 were found to be 49.6 μM and 20.1 μM, respectively. Abstract : Anthraimidazoledione derivatives 1 and 2 with silyl groups are designed and synthesized. They exhibit F − binding with reference to Si−O bond cleavage in organic and aqueous medium. Both 1 and 2 selectively sense F − ion over a series of other anions by exhibiting ratiometric change in UV‐vis spectra in CH3 CN. In fluorescence, quenching of emission of both 1 and 2 occurs in presence of F − . Detection limits are found to be 49.6 μM and 20.1 μM for 1 and 2, respectively.